Exploring the mediating role of the non-high-density lipoprotein cholesterol to high-density lipoprotein cholesterol ratio (NHHR) in the association between obesity and sleep-disordered breathing - Ying Cui; Ziyi Cheng (Eating and Weight Disorders)
Abstract Purpose Exploring novel mediators affecting the relationship between obesity and sleep-disordered breathing (SDB) is necessary. This study aimed to explore the mediating role of the non-high-density lipoprotein cholesterol to high-density lipoprotein cholesterol ratio (NHHR) in the association between body mass index (BMI) and SDB using data from the 2015–2018 National Health and Nutrition Examination Survey (NHANES) cycles. Methods Total 7639 participants were included. SDB was defined based on the self-reported frequency of snoring, snorting, or excessive daytime sleepiness. The BMI and NHHR were calculated based on height and weight measurements and laboratory data, respectively. Weighted multivariate logistic and linear regression analyses were conducted to examine the associations, and restricted cubic spline (RCS) analysis was used to assess dose–response relationships. Mediation analysis was performed to evaluate the NHHR’s role in the BMI–SDB association. Subgroup analyses were performed to assess differences across various populations. Results SDB symptoms were observed in 51.05% of participants. Higher BMI was significantly associated with increased SDB risk. RCS analysis revealed a nonlinear relationship between BMI and SDB. Subgroup analyses indicated a positive correlation between BMI and SDB was stronger among nonhypertensive participants. NHHR was positively associated with BMI and SDB. Mediation analysis showed that the NHHR explained 5.44–8.12% of the BMI–SDB association. Conclusions BMI is a critical factor in the risk of SDB, and the NHHR partially mediates this relationship. BMI and cholesterol levels should be managed to mitigate the SDB risk. Level of evidence Level V—cross-sectional observational study.